The International configuration in the post-Covid 19 era from constructivism’s perspective view - Sun, Rachel (Advances in Social Sciences Research Journal, 2021)
The global outbreak of Covid-19 pneumonia in 2020 has instantly changed the appearance of the world and caused a sudden change in the interaction pattern of international actors. Actors at all levels have survived the current situation for more than a year under the premise of being forced to change. However, actors at all levels who are unwilling to succumb to the impact of the current epidemic are aiming to restore their pre-epidemic lifestyles, and are drawing up plans to rebuild the international order and respond to new challenges, including the current vaccine policies of various countries-how to respond appropriately demands on a global scale. Therefore, all past political and democratic issues have been repositioned in the post-epidemic era of environmental changes to be verified again. Most members of the international community have strengthened multilateralism in their cooperation in the fight against the epidemic. However, the Trump administration's “America First” and unilateralism pose the greatest challenge to the international multi-polarization pattern and a fair and reasonable world order. Therefore, analyzing and studying changes in the international pattern and world order under the epidemic will help improve practice and theoretical consciousness, and promote the construction of contemporary new international relations and a community with a shared future for mankind. This article attempts to analyze the international configuration in the post-Covid 19 era from the perspective of Windt's constructivism.